Exploring the job demands experienced by employees with hearing impairment in South Africa - Strauss Chelius; Bouwer E. Jonker; Marissa Brouwers (SA Journal of Human Resource Management, 2022)
Orientation: South Africa’s employment equity agenda towards persons with disabilities requires more insight to develop polices and standards of practice.